Synthesis and biological evaluation of new 13-n-nonylprotoberberine derivatives as antitubercular agents - Yinghong Li; Yanxin Liu; Yanxiang Wang; Sheng Tang; Danqing Song (Elsevier, 2013)
Tuberculosis is a serious threat to public health throughout the world. A series of new 13-n-nonylprotoberberine derivatives was designed, synthesized and evaluated for anti-mycobacterial activity against Mycobacterium tuberculosis strain H37Rv. Several compounds (2, 11a-c, 11g, 13d, 15c) exhibited excellent anti-tubercular activity with an MIC below 1.0μg/mL. Notably, compound 13d showed potential antibacterial effect against both drug-susceptible and multidrug-resistant (MDR) M. tuberculosis with MIC ranges of 0.0625-1.0 μg/mL. These results suggest a mode of action different from that of the current anti-mycobacterial drugs rifampicin and isoniazid. Hence, compound 13d is an attractive lead compound for the development of new antitubercular agents.